Research progress of Gastrodia elata Blume polysaccharides: a review of chemical structures and biological activities - Yang, Liu; Qin, Shi-Hui; Zi, Cheng-Ting (Frontiers in Chemistry, 2024)
Gastrodia elata Blume (G. elata), listed as one of the 34 precious Chinese medicines, servers a dual purpose as both a medicinal herb and a food source. Polysaccharide is the main active ingredient in G. elata, which has pharmacological activities such as immune regulation, anti-oxidation, anti-cancer, anti-aging, neuroprotection and antibacterial activity and so on. The biological activities of G. elata polysaccharide (GPs) is closely related to its chemical structures. However, no a review has synthetically summarized the chemical structures and pharmacological activities of GPs. This study delves into the chemical structures, pharmacological action of GPs, offering insights for the future development an application of these compounds.